Antiphospholipid antibodies as potential predictors of disease severity and poor prognosis in systemic lupus erythematosus-associated thrombocytopenia: results from a real-world CSTAR cohort study - Li, Jun; Peng, Liying; Wu, Lijun; Ding, Yufang; Duan, Xinwang; Xu, Jian; Wei, Wei; Chen, Zhen; Zhao, Cheng; Yang, Min; Jiang, Nan; Zhang, Shangzhu; et al. (Arthritis research & therapy, 2024)
To investigate the role of antiphospholipid antibodies (aPLs) in the disease severity and prognosis of SLE-related thrombocytopenia (SLE-TP). This multicenter prospective study was conducted based on data from the CSTAR registry. TP was defined as a platelet count<100 × 10 /L. Demographic characteristics, platelet count, clinical manifestations, disease activity, and autoantibody profiles were collected at baseline. Relapse was defined as the loss of remission. Bone marrow aspirate reports were also collected. A total of 350 SLE-TP patients with complete follow-up data, 194 (55.4%) were aPLs positive. At baseline, SLE-TP patients with aPLs had lower baseline platelet counts (61.0 × 10 /L vs. 76.5 × 10 /L, P<0.001), and a higher proportion of moderate to severe cases (24.2% vs. 14.1% ; 18.0% vs. 8.3%, P<0.001). SLE-TP patients with aPLs also had lower platelet counts at their lowest point (37.0 × 10 /L vs. 51.0 × 10 /L, P = 0.002). In addition, thean increasing number of aPLs types was associated with a decrease in the baseline and minimum values of platelets ( P<0.001, P = 0.001). During follow-up, SLE-TP carrying aPLs had a higher relapse rate (58.2% vs. 44.2%, P = 0.009) and a lower complete response (CR) rate. As the types of aPLs increased, the relapse rate increased, and the CR rate decreased. Furthermore, there was no significant difference in the ratio of granulocytes to red blood cells (G/E), the total number of megakaryocyte and categories. SLE-TP patients with positive aPLs had more severe disease a lower remission rate but a higher relapse rate.